Internalization of Cultural Values and Nationalism Characteristics of Ki Hajar Dewantara's Thoughts on "Gen Z" in the Era of Society 5.0. Case study: Indonesian schools in the Netherlands, Singapore and Malaysia - Wike Agung Safitri (Experimental Student Experiences, 2022)
Internalization of Indonesian culture is an effort made to instill a person's character and character so that it reflects a behavior that describes his identity as an Indonesian citizen. Indonesian youth who live in other countries generally have a mixed culture between Indonesian culture and the culture of the country where they live. Indonesian overseas schools or commonly abbreviated as SILN is one of the state's responsibilities and a form of state concern for the younger generation who live and temporarily settle abroad so that they can continue to receive the same education as in Indonesia. The purpose of this research is to provide information about the cultural values ​​and behavior of nationalism instilled in foreign Indonesian schools, especially in the Netherlands, Singapore and Malaysia. The method used in this study is a literature study. The results showed that cultural values ​​and nationalism were instilled in Indonesian schools in Malaysia, Singapore and the Netherlands through extracurricular activities in the form of Indonesian traditional arts, traditional musical instruments and traditional dances, and learning in the classroom including politeness, hospitality, and democratic attitudes.